Evaluation of Systematic Blood Testing at the Time of Recruitment to the Armed Forces: Retrospective Monocentric Study Among 726 French Army Soldiers. Issue 3 (28th October 2019) - Caré, Weniko; Hénard, Jessica; Gillard, Jonathan; Cremades, Serge; Ceppa, Franck; Vest, Philippe; Foissaud, Vincent; Hejl, Carine
Abstract: Introduction: In the French armed forces, the biological checkup required during the recruitment process comprises a urinalysis (urinary dipstick), a complete blood count (CBC), and measurement of serum levels of aspartate aminotransferase, alanine aminotransferase, fasting blood glucose, and creatinine. This study aimed to evaluate the benefits of this biological checkup and to determine the most relevant parameters. Materials and Methods: We conducted a monocentric retrospective study of all standardized and systematically conducted blood tests (CBC and measurement of aspartate aminotransferase, alanine aminotransferase, fasting blood glucose, and creatinine) over a 15-month period among 726 French Army recruits. Results: The population included mainly young males (85.4%, mean age 21.6 years). More than half (54.1%) of the blood tests had at least one abnormal parameter, most often concerning the CBC. Anemia occurred in 5.3% of the population and was mostly normocytic. Microcytosis was mostly not associated with anemia (72.3% of cases). Lymphopenia occurred in 20.1% of the population and was mostly mild. Eosinophilia was present in 5.1% of the population and was never severe. Thrombocytopenia occurred in 0.7% of the population and was never severe. Serum levels of aminotransferases were elevated in 8.1% of the population. Fasting plasma glucose averaged 84 mg/dL (SD: 0.07) ranging from 64 to 123 mg/dL, was abnormal in 0.4% of the population, and one case of diabetes was diagnosed. Serum creatinine concentration was elevated in 0.7% of the population. Conclusion: CBCs gave useful information but iron deficiency was common and insufficiently detected by this single analysis. Assessing aminotransferase levels without screening for viral hepatitis and systematic measurement of fasting plasma glucose levels did not appear to be efficient. In addition, the only interest in systematic measurement of creatinine serum levels was to obtain a reference level for long-term follow-up. In addition to the urinary dipstick, the systematic biological checkup at recruitment could be limited to a CBC with measurement of plasma ferritin levels and Hepatitis B virus serology, providing that any CBC abnormalities, in particular cytopenia, eosinophilia, and microcytosis, are systematically investigated. For a public health approach, systematic screening for other sexually transmitted infections could be proposed.